The Ethnographic Department of the Russian Museum in the Realities of So-cial-Political life in the 1920s and 1930s - Natalia I. Ivanoskaya (Историческая этнология, 2021)
The article is devoted to the one of the most important problems in the history of museum studies, namely the state museum policy. Museums participate in the histori-cal and cultural process, relying not only on the concepts and the objectives of academic disciplines, but on the public needs of a particular historical era and the influence of power structures as well. The purpose of the study is to analyze the influence of state ideological attitudes on the research works in the field of museum ethnography and on personal fates of employees of the Russian Museum Ethnographic Department in the 1920s and 1930s, using archival sources. The author introduces into scientific circula-tion previously classified directive documents which regulated museum activities during that period. Considerable attention is paid to the study of the museum employees’ field reports which give an indication of the shift in the methodological approach to ethno-graphic studies at the time. The paper involves personal archival documents which shed a light on the details of everyday life and lifestyle, the nature of relationships between people, determined by the political organization of society, among other things.The study leads to the conclusion that the powerful ideological pressure of the state that took place during those years negatively influenced not only ethnography and museol-ogy disciplines turning them into an instrument of socialist propaganda for a certain period of time, but led many ethnographers to tragic fate.